2003
DOI: 10.1016/s0375-9474(03)01480-5
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear response functions for the N– transition

Abstract: Parity-conserving and -violating response functions are computed for the inclusive electroexcitation of the N * (1440) (Roper) resonance in nuclear matter modeled as a relativistic Fermi gas. Using various empirical parameterizations and theoretical models of the N − N * (1440) transition form factors, the sensitivity of the response functions to details of the structure of the Roper resonance is investigated. The possibility of disentangling this resonance from the contribution of ∆ electroproduction in nucle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 40 publications
(59 reference statements)
2
36
0
Order By: Relevance
“…[41]). Whereas L data are compatible with superscaling behavior, permitting the extraction of the phenomenological function f exp L (ψ ), scaling is known to be violated in the T channel at energies above the QE peak by effects beyond the impulse approximation [20][21][22][23][24]84]. It is important to point out that, although many models based on the impulse approximation exhibit superscaling, even perfectly as the RFG, only a few of them are capable to accurately reproduce the asymmetric shape of f exp L with a significant tail extended to high transferred energies (large positive values of the scaling variable ψ ).…”
Section: A Scaling At the Quasielastic Peakmentioning
confidence: 97%
“…[41]). Whereas L data are compatible with superscaling behavior, permitting the extraction of the phenomenological function f exp L (ψ ), scaling is known to be violated in the T channel at energies above the QE peak by effects beyond the impulse approximation [20][21][22][23][24]84]. It is important to point out that, although many models based on the impulse approximation exhibit superscaling, even perfectly as the RFG, only a few of them are capable to accurately reproduce the asymmetric shape of f exp L with a significant tail extended to high transferred energies (large positive values of the scaling variable ψ ).…”
Section: A Scaling At the Quasielastic Peakmentioning
confidence: 97%
“…However, the present experimental status does not allow any conclusions on the strange transition form factors, thus, we neglect them in this work and set F s i and F s A to zero. Several studies have addressed the properties of the P 11 (1440) as well as its electromagnetic and weak production [40,41,42,43,44,45,46,47]. In the works of Refs.…”
Section: Excitation Of Spin 1/2 Resonancesmentioning
confidence: 99%
“…An exhaustive analysis of (e, e ) world data demonstrated the scaling at energy transfers ω below the quasielastic (QE) peak [1,2], namely the independence of the reduced cross sections on the momentum transfer (first-kind scaling) and on the nuclear target (second-kind scaling) when plotted versus the appropriate scaling variable. It is well known that at energies above the QE peak scaling is violated in the transverse (T ) channel by effects beyond the impulse approximation: inelastic scattering [3,4], correlations, and meson-exchange currents (MEC) in both the one-particle one-hole (1p-1h) and two-particle two-hole (2p-2h) sectors [5][6][7][8].In contrast, the available data for the longitudinal (L) response are compatible with scaling throughout the QE region and permitted [9] the extraction of a phenomenological scaling function f L . In recent work [10][11][12] it was shown that only a few models [the relativistic mean field (RMF), the semirelativistic (SR) approach with Dirac-equation-based (DEB) and a "BCS-like" model] are capable of reproducing the detailed shape of f L , while other models fail to reproduce the long tail appearing at high ω. Theses models effectively account for the major ingredients needed to describe the (e, e ) responses for intermediate-to-high momentum transfers, namely relativistic effects and an appropriate description of the effective final-state interactions (FSI).…”
mentioning
confidence: 99%
“…An exhaustive analysis of (e, e ) world data demonstrated the scaling at energy transfers ω below the quasielastic (QE) peak [1,2], namely the independence of the reduced cross sections on the momentum transfer (first-kind scaling) and on the nuclear target (second-kind scaling) when plotted versus the appropriate scaling variable. It is well known that at energies above the QE peak scaling is violated in the transverse (T ) channel by effects beyond the impulse approximation: inelastic scattering [3,4], correlations, and meson-exchange currents (MEC) in both the one-particle one-hole (1p-1h) and two-particle two-hole (2p-2h) sectors [5][6][7][8].…”
mentioning
confidence: 99%